The comparison of capillary zone electrophoresis and atomic spectroscopy for the determination of the cation content of a standard reference material IAEA-A-11 milk powder - Pretswell, Emma L.; McGaw, Brian A.; Morrisson, Andrew R. (Talanta (Oxford), 1995)
Alkali and alkaline earth metals were separated and quantified by Capillary Zone Electrophoresis using a previously developed method. CZE combined with indirect detection has received considerable attention over the last few years. Methods for the determination of inorganic and organic cations and anions have been reported although few of these include quantitative application to real samples. All of these methods are characterized by high efficiencies and high capacity. Application of the method to the determination of the major cation content of an International Atomic Energy Agency (IAEA) standard reference material is described. Complete resolution and quantitation of the ions (Na +, K +, Ca 2+, Mg 2+) was achieved with calibration curves, for the individual components, having correlation coefficients ( r 2) ranging from 0.996 to 0.999 and detection limits (two times the baseline noise) of 10 ppb for potassium and magnesium and of 2.5 ppb for sodium and 2 ppb for calcium were achieved. Comparable results were achieved when employing analysis by Atomic Spectroscopy. The accuracy of this method was tested by comparison with standard flame Atomic Absorption cation analysis. Statistical analysis of the instrumental results indicate that there is no evidence suggesting systematic differences between the methods. In addition, a number of potential advantages of CZE for cation analysis are discussed.